PENGEMBANGAN MODEL PENILAIAN FORMATIF DENGAN SOAL ISOMORFIK BERBANTUAN KOMPUTER UNTUK MENINGKATKAN PENGUASAAN KONSEP FISIKA SISWA SMP - Trisusiyanti S.Si, Indri (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
Formative assessment is very important for student‟s learning. Formative assessment is used to help students learning. Student can know student‟s abilities and weaknesses. The formative assessment combined with isomorphic problems can know more how far student‟s mastery concept. In the real, giving information to student by teacher tends to take a long time, non-optimal, and unintensive because of large number of students. Formative assessment model needs to be improved with computerized program, in order to be efective and efficient assessment for student and teacher. Research uses procedure which is adapted by Borg & Gall procedure. Subjects of research are 40 the-8th-grade-students at SMPK Kolese Santo Yusup 2 Malang. Data of research consists of quantitative data (comparation of pretest score and postest score) and be analized with t-test. Assessment of product is done by 5 validators, such as 1 expert of assessment, 1 expert of physics, 1 expert of information technology and 2 physics of teachers. Advisability assessment data is quantitative data with Likert scale and qualitative data is validator‟s advises. Product application which is used to test effectivity of product shows effective result for students and not yet effective result for teacher. Non-efective for teacher is teacher cannot know whether the results is reliable because teacher cannot supervise the students using the product from start until finish. Keywords: formative assessment, model, isomorphic problem, computer, mastery concept, student’s learning.